Developing an economic complexity-based digital decision support tool for South African industrial policy masterplans - Du Plessis, Michael Jacobus (Stellenbosch : Stellenbosch University, 2025)
Du Plessis, M. J. 2025. Developing an Economic Complexity-based Digital Decision Support Tool for South African Industrial Policy Masterplans. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/ecc81372-22f8-4e94-9b27-5b97306af4bf